Pengaruh Locus of Control, Kepemimpinan Transformasional dan Spiritual At Work Terhadap Kinerja Karyawan - Darmawan, Akhmad; Bagis, Fatmah; Anggraini, Intan Anggun Puspita (BISNIS, 2021)
This study aims to determine the effect of locus of control, transformational leadership and spiritual work on employee performance (Case study on employees of Perum Perhutani KPH East Banyumas). The population of 145 people who are employees of the production division of Perum KPH Banyumas Timur and the sample used in this study amounted to 145 samples. The sampling technique used was the purposive sampling method. The research used a questionnaire. The results of this study are based on data analysis using multiple linear regression test and coefficient of determination test. 1.Locus Of Control, transformasional leadership and work spiritually have a simultaneous effect on perfomance perum perhutani KPH east Banyumas. 2.Locus Of Control has a significant effect on performance perum perhutani KPH  east Banyumas. 3.significant transformational leadership to words performance perum perhutani KPH east Banyumas. 4.work spiritual have a significant effect on performance perum perhutani KPH east Banyumas.